Prospects for the development of rural labor resources under the impact of changes in the rural areas economy in the 2020s - E. A. Yugov (Вестник университета)
The paper presents the stages of changes in the development of labor resources in rural areas in the post-Soviet period, which prepared them for further transformations. The author identifies as the main directions of changes that may occur in the 2020s in the economy of rural areas and will affect the labor resources of rural areas: the active introduction of digital technologies and artificial intelligence in agricultural production; the emergence of new rural professions and specialties and associated modernization of the personnel training system; transformation of employment of rural labor resources in connection with technological transformations in the economy; the new approach on the part of employers to social and labor relations with labor resources associated with the changes in the technological structure in rural areas; development of a modern organizational and technological paradigm for the development of the rural economy. It is assumed that the rural labor force will need new adaptation, which will be natural and will take place in a milder form.